Bioavailability of Orally Administered Drugs After Bariatric Surgery - Dvořáčková, Eliška; Pilková, Alena; Matoulek, Martin; Slanař, Ondřej; Hartinger, Jan (Current obesity reports, 2024)
PURPOSE OF REVIEW: Oral drug absorption after bariatric surgery is likely to be altered, but the impact of different bariatric surgery procedures on individual drugs is not uniform. The aim of this article is to describe factors influencing the bioavailability of orally administered drugs after bariatric surgery and to provide readers with practical recommendations for drug dosing. We also discuss the medications that may be harmful after bariatric surgery. RECENT FINDINGS: The fundamental factors for enteral drug absorption are the production of gastric acid; the preserved length of the intestine, i.e., the size of the absorption surface and/or the preserved enterohepatic circulation; and the length of common loop where food and drugs are mixed with digestive enzymes and bile acids. Bypassing of metabolizing enzymes or efflux pumps and changes in intestinal motility can also play an important role. Significant changes of drug absorption early after the anatomic alteration may also be gradually ameliorated due to gradual intestinal adaptation. The most affected drugs are those with low or variable bioavailability and those undergoing enterohepatic circulation. Attention should also be paid to oral drug formulations, especially in the early postoperative period, when immediate-release and liquid formulations are preferred. The changes in oral bioavailability are especially clinically meaningful in patients treated with drugs possessing narrow therapeutic index (e.g., oral anticoagulants, levothyroxine, and anticonvulsants) or in acute conditions (e.g., anti-infectives); nevertheless, it may also influence the therapeutic value of chronic therapy (e.g., antidepressants. antihypertensives, antiplatelets, statins, PPIs, contraceptives, and analgesics); therapeutic effect of chronic therapy is further influenced by pharmacokinetic alterations resulting from weight loss. Therapeutic drug monitoring, periodical clinical evaluation, and adequate dose adjustments are necessary. Due to safety reasons, patients should avoid oral bisphosphonates, regular use of non-steroidal anti-inflammatory drugs, and, if possible, corticosteroids after bariatric surgery.
Keywords: gastrektomie; Bariatric Surgery; bariatrická chirurgie; Weight Loss; morbidní obezita; Biological Availability; hmotnostní úbytek; biologická dostupnost; žaludeční bypass; lidé; Gastrectomy; Obesity, Morbid; Humans; Gastric Bypass